BLOG WRITING AS A MEDIUM FOR ENGLISH SKILL DEVELOPMENT: IDENTIFYING GRAMMATICAL ERRORS AND LEXEME SELECTION - Mutiara Shal Sabillah; Evi Agustina Sari; Tiur Simanjuntak; Munaja Rahma; Moehamad Ridhwan (Language and Education Journal, 2025)
This study investigates blog writing as a dual-purpose medium for developing English language skills while serving as a promotional tool for Kopi 16Pro through the blog script titled "Ampera's Scenic Charm in Kopi 16Pro." Employing the Research and Development (R&D) method, the research identifies grammatical errors and lexeme selection in the blog script to enhance its linguistic accuracy and promotional effectiveness. Data were gathered through error analysis of the blog text, interviews with language experts, and feedback from potential readers. The findings reveal common grammatical issues and inappropriate lexeme use, which were addressed through iterative revisions, significantly improving the script's quality. The blog is a resource for tourists seeking information about tourism destinations, explicitly aiming to facilitate the easy discovery of Kopi 16Pro Palembang. The blog was uploaded on July 9, 2024; after 5 days of being uploaded, the blog received 80 views and several positive comments, such as "what a nice view" and "so informative and cannot wait to go there.” Finally, it concludes that blog writing can effectively develop language skills and promote business. Further research is recommended to explore integrating creative writing into educational curricula and marketing strategies